Combination checkpoint therapy with anti-PD-1 and anti-BTLA results in a synergistic therapeutic effect against murine glioblastoma. (1st January 2021) - Choi, John; Medikonda, Ravi; Saleh, Laura; Kim, Timothy; Pant, Ayush; Srivastava, Siddhartha; Kim, Young-Hoon; Jackson, Christina; Tong, Luqing; Routkevitch, Denis; Jackson, Christopher; Mathios, Dimitrios; et al.
ABSTRACT: Clinical trials involving anti-programmed cell death protein-1 (anti-PD-1) failed to demonstrate improved overall survival in glioblastoma (GBM) patients. This may be due to the expression of alternative checkpoints such as B- and T- lymphocyte attenuator (BTLA) on several immune cell types including regulatory T cells. Murine GBM models indicate that there is significant upregulation of BTLA in the tumor microenvironment (TME) with associated T cell exhaustion. We investigate the use of antibodies against BTLA and PD-1 on reversing immunosuppression and increasing long-term survival in a murine GBM model. C57BL/6 J mice were implanted with the murine glioma cell line GL261 and randomized into 4 arms: (i) control, (ii) anti-PD-1, (iii) anti-BTLA, and (iv) anti-PD-1 + anti-BTLA. Kaplan–Meier curves were generated for all arms. Flow cytometric analysis of blood and brains were done on days 11 and 16 post-tumor implantation. Tumor-bearing mice treated with a combination of anti-PD-1 and anti-BTLA therapy experienced improved overall long-term survival (60%) compared to anti-PD-1 (20%) or anti-BTLA (0%) alone ( P = .003). Compared to monotherapy with anti-PD-1, mice treated with combination therapy also demonstrated increased expression of CD4+ IFN-γ ( P < .0001) and CD8+ IFN-γ ( P = .0365), as well as decreased levels of CD4+ FoxP3+ regulatory T cells on day 16 in the brain ( P = .0136). This is the first preclinical investigation into the effects of combination checkpoint blockade with anti-PD-1 and anti-BTLA treatment in GBM. We also show a direct effect on activated immune cell populations such as CD4+ and CD8 + T cells and immunosuppressive regulatory T cells through this combination therapy.